George Barton and the Art of Friendship - McKenzie, Peter (Victoria University of Wellington Law Review, 2012)
This article contains the text of an address given at the sitting of the High Court in Wellington for Dr George Barton QC by Peter McKenzie on 6 July 2011. Peter McKenzie QC was from 1966 to 1976 a colleague of Dr Barton's on the Law Faculty of Victoria University of Wellington. McKenzie remembers Dr Barton, both as a legal colleague and a friend.